Growth performance and digestive enzymes activity of Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) feeding on six rice cultivars. (June 2019) - Ebadollahi, Asgar; Borzoui, Ehsan
Abstract: The lesser grain borer, Rhyzopertha dominica (F.), is one of the major insect pests of stored-grains such as wheat and rice. Due to various difficulties associated with synthetic pesticides, more environmentally friendly alternative methods are greatly appreciated for controlling pests. In the present study, development, growth index, reproductive success of the females and the amylolytic and proteolytic activities of R. dominica were investigated on six rice cultivars. The experiments were carried out under laboratory conditions inside a growth chamber, which was set at 28 °C, 70% R.H. Our results showed that cultivar Hashemi was the more suitable host for R. domininica because the highest larval and pupal survival rate, longevity of adults, fecundity, hatchability of females, food consumption, maximal growth index, as well as the highest amylolytic and proteolytic activities. In contrast, cultivar Gohvar showed the most suitable suite of traits to reduce potential aspects of feeding by R. domininica because the lowest larval and pupal survival rate, adult longevity, fecundity, hatchability, and lower adult weight and food consumption. Results suggested that cultivar Govhar cultivar as an unsuitable host for R. domininica could be considered in the integrated management of this pest. Graphical abstract: Image 1 Highlights: Rhyzopertha dominica (F.) is one of the major insect pests of stored-grains. The highest adult longevity and the highest fecundity females were observed on cultivar Hashemi. The maximal growth index of larvae was gained on cultivar Hashemi. Adults reared on cultivar Hashemi also showed the highest amylolytic and proteolytic activities. Results suggested that Govhar cultivar as an unsuitable host could be considered in the integrated management of this pest.